Utilizing Theories and Evaluation in Digital Gaming Interventions to Increase Human Papillomavirus Vaccination Among Young Males: Qualitative Study - Darville, Gabrielle (JMIR Serious Games, 2021)
BACKGROUND: Human papillomavirus (HPV) is the most common sexually transmitted infection in the United States. HPV attributes to most cancers including anal, oral, cervical, and penile. Despite infection rates in the United States, recommendations and communication campaigns have traditionally focused on females. Because of this, males lack knowledge about reasons for vaccination, the benefits of being vaccinated, and their HPV risk, overall. Gaming as a health education strategy can be beneficial as mechanism that can promote behavior change for this key demographic because of the popularity of gaming. OBJECTIVE: We sought to explore the relationship between gamification and HPV vaccine uptake. METHODS: Interviews were conducted with experts (n=22) in the fields of cancer prevention, sexual and reproductive health, public health, game design, technology, and health communication on how a game should be developed to increase HPV vaccination rates among males. RESULTS: Overwhelmingly, theoretical models such as the health belief model were identified with key constructs such as self-efficacy and risk perception. Experts also suggested using intervention mapping and logic models as planning tools for health promotion interventions utilizing a digital game as a medium. In game and out of game measures were discussed as assessments for quality and impact by our expert panel. CONCLUSIONS: This study shows that interventions should focus on whether greater utilization of serious games, and the incorporation of theory and standardized methods, can encourage young men to get vaccinated and to complete the series of HPV vaccinations.